Myofibroblastoma of the Breast: Literature Review and Case Report - Mario Metry; Mohamad Shaaban; Magdi Youssef; Michael Carr (Case Reports in Oncological Medicine)
Myofibroblastoma of the breast is a rare benign spindle cell tumor. The main aim of this study is to review the literature of this rare tumor. We present a case of a mammary myofibroblastoma occurring in an 82-year-old man, emphasizing the clinical, radiological, and pathological features. The tumor was successfully identified and managed in our hospital. We would like to draw the attention of clinicians to myofibroblastoma as a rare possibility in the differential diagnosis of a breast mass.